Beauty and cuteness in peripheral vision - Kuraguchi, Kana; Ashida, Hiroshi (Frontiers in Psychology, 2015)
Guo, Liu, & Roebuck (2011) showed that attractiveness was detectable in peripheral vision. Since there are different types of attractiveness (Rhodes, 2006), we investigated how beauty and cuteness are detected in peripheral vision with a brief presentation. Participants (n = 45) observed two Japanese female faces for 100 ms, then were asked to respond which face was more beautiful (or cuter). The results indicated that both beauty and cuteness were detectable in peripheral vision, but not in the same manner. Discrimination rates for judging beauty were invariant in peripheral and central vision, while discrimination rates for judging cuteness declined in peripheral vision as compared with central vision. This was not explained by lower resolution in peripheral vision. In addition, for male participants, it was more difficult to judge cuteness than beauty in peripheral vision, thus suggesting that gender differences can have a certain effect when judging cuteness. Therefore, central vision might be suitable for judging cuteness while judging beauty might not be affected by either central or peripheral vision. This might be related with the functional difference between beauty and cuteness.